The Effect of Debt to Equity Ratio and Return on Equity on Stock Price in Jakarta Islamic Index Companies on Indonesia Stock Exchange Period 2015-2019 - Juwita, Chairunisa Puspa; Diana, Nana (Universitas Negeri Semarang, 2020)
The main purpose of this study is to test the effect of Debt to Equity Ratio (DER) and Return on Equity Ratio (ROE) on Stock Price in the Jakarta Islamic Index Companies period 2015-2109. This study used quantitative research by using a purposive sampling method and obtained 12 samples. The data obtained by the annual company financial report of JII companies during 2015-2019. The method used is descriptive statistical analysis through the classical assumption test to analyze data and multiple linear regression. Data testing used SPSS Statistics 22. The result of this study shows DER does not affect the stock price partially and ROE has a significant positive effect on the stock price while simultaneously debt to equity ratio and return on equity affect the stock price.